Making sense of heritability - Sesardić, Neven, 1949- (Cambridge studies in philosophy and biology., 2005)
Neven Sesardic defends the view that it is both possible and useful to measure the separate contributions of heredity and environment to the explanation of human psychological differences. His book is a fresh, original and compelling intervention in a very contentious debate.